The 3d Printability and Mechanical Properties of Polyhydroxybutyrate (PHB) as Additives in Blends Polymer for 3d Printed Arm Cast - Ahmad Adnan bin Abu Bakar (Universiti Sains Islam Malaysia, 2024)
Matric: 3201064 (FST)